2018
DOI: 10.1186/s13018-018-0919-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of K-wire tension band fixation compared with other alternatives for patella fractures: a meta-analysis

Abstract: BackgroundTo compare the efficacy and safety of K-wire tension band fixation (KTB) with other alternative approaches (cannulated screws, cable pin, and ring pin) for treatment of patella fractures by performing a meta-analysis.MethodsPubMed and EMBASE databases were searched for all relevant studies. Standardized mean difference (SMD) or relative risk (RR) and their corresponding 95% confidence intervals (CIs) were calculated for continuous or dichotomous outcomes via either a fixed- or random-effect model usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
2
23
0
1
Order By: Relevance
“…Generally speaking several surgical treatment options are available according to the fracture type using the AO classification. Open or closed fixation using tension band wiring with its modifications as well established techniques for transverse fractures of the patella are widely used [17][18][19]. Dy et al reported in their meta-analysis about several complications of tension band wiring resulting in a less functional outcome and high revision rates in up to one-third of all patients including loss of reduction and secondary dislocation, implant failure or implant discomfort [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking several surgical treatment options are available according to the fracture type using the AO classification. Open or closed fixation using tension band wiring with its modifications as well established techniques for transverse fractures of the patella are widely used [17][18][19]. Dy et al reported in their meta-analysis about several complications of tension band wiring resulting in a less functional outcome and high revision rates in up to one-third of all patients including loss of reduction and secondary dislocation, implant failure or implant discomfort [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Tension band with cannulated screw had a better curative effect on patella fracture, lower complication rate, and higher quality of life of patients. A meta-analysis report showed that there was no difference in the success rate of operation, operation time, fracture healing time, and the number of infections between the cannulated screw and Kirschner wire tension band in treating patella fracture, but cannulated screw tension band was superior to Kirschner wire tension band in reducing the incidence of complications [ 20 ]. In the internal fixation of patella fracture, biodegradable implants were not as effective as metal implants in the treatment of displaced patella fracture, but implant stimulation was the main reason for the second operation, and the removal rate of symptomatic implants after treatment with cannulated screw tension band was low (8%) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,23,25 Although there are some complications associated with migration of K-wire, TBWKW has been shown sufficient stability for a bone union. 26 In results of this study, TBWKW and TBWRP were proven enough clinical stability.…”
Section: Discussionmentioning
confidence: 60%
“…Although the TBWRP group showed similar fixation strength to TBWKW group, the clinical results of TBWRP are reported to be superior to TBWKW because of stationary implant. 26 Kim et al 14 reported TBWRP to have 100% union rate with 0% pin migration with pin removal rate of 8.3%, which is lower than the previously reported outcome of MTBW. Kyung et al 15 also reported 100% union rate and migration rate, which was statistically superior to TBWKW technique.…”
Section: Discussionmentioning
confidence: 75%